2022
DOI: 10.3389/fnins.2022.957667
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-interacting protein in diabetic retinal neurodegeneration: A novel potential therapeutic target for diabetic retinopathy

Abstract: Diabetic retinopathy (DR) is a common complication of diabetes mellitus and has been considered a microvascular disease for a long time. However, recent evidence suggests that diabetic retinal neurodegeneration (DRN), which manifests as neuronal apoptosis, a decrease in optic nerve axons, and reactive gliosis, occurs prior to retinal microvascular alterations. Thioredoxin-interacting protein (TXNIP) is an endogenous inhibitor of thioredoxin (Trx), and it acts by inhibiting its reducing capacity, thereby promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…Mitigating OXS was previously reported to decrease hyperglycemia-induced neuronal damage [4]. In addition, proper glutamate metabolism was found to be crucial for the maintenance of retinal health [5]. Diabetes could contribute to glutamate accumulation in the retina, which eventually leads to the hyperexcitation of N-methyl-D-aspartate receptors (NMDARs), enhancement of calcium influx and retinal neurodegeneration [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitigating OXS was previously reported to decrease hyperglycemia-induced neuronal damage [4]. In addition, proper glutamate metabolism was found to be crucial for the maintenance of retinal health [5]. Diabetes could contribute to glutamate accumulation in the retina, which eventually leads to the hyperexcitation of N-methyl-D-aspartate receptors (NMDARs), enhancement of calcium influx and retinal neurodegeneration [6].…”
Section: Introductionmentioning
confidence: 99%
“…At present, three drugs have been approved by the US Food and Drug Administration for DREN, namely ranibizumab, pegaptanib and aflibercept. They decrease the rate of retinal deterioration [5]. Ranibizumab and aflibercept are administered as an intravitreal injection into the eye.…”
Section: Introductionmentioning
confidence: 99%
“…Statistically, the ratio of blindness caused by DR ranged from 15-17% in developed areas [4]. Notably, it is reported that oxidative stress, apoptosis, and inflammation can promote the development of DR [5,6]. Studies in diabetic mice demonstrated that inflammatory processes aggravated the occurrence of DR by upregulating the expression of pro-inflammatory cytokine [7].…”
Section: Introductionmentioning
confidence: 99%